Numerical investigation of twin-liquid film on spoked rotating disk reactor with highly viscous fluid. (29th June 2022) - Li, Leqi; Xie, Hanguang; He, Long; Deng, Bin; Zong, Yuan; Yang, Xiaogang; Zhao, Ling; Dai, Gance
Highlights: Twin-liquid film flow has been observed on a spoked rotating disk reactor. Interplay between the confined free film and wall-bounded film leads to mass transfer intensification. The circumferential length of the opening window should be accommodated to fluid viscosity. Abstract: Spoked rotating disk reactor is a common gas–liquid mass transfer equipment for highly viscous fluids. The hydrodynamics of the twin-liquid film on the disk is numerically investigated. The simulated film thickness, which agrees well with the experimental results, shows that film flow patterns shift at different rotational speeds. The alternation between the windows and spokes brings diverse film flow pattern, i.e., twin-liquid film, where a confined free film and a wall-bounded film coexist and interplay. The twin-liquid film results in 70% thinning of the film thickness and 30% increase in the surface renewal frequency compared to the wall-bounded film. Based on the trajectory of the tracking particles, intense velocity fluctuations within the twin-liquid film can be observed. Given the pressure gradient within the opening window increasing exponentially with fluid viscosity, we suggest that the circumferential length of the open window be proportional to fluid viscosity. The results demonstrate good adaptability of the optimization strategy, which can guide the scaling-up of the spoked rotating disk reactors for highly viscous fluids.